The kitsch paradox – the life and the art of Ed Wood as the example of the success of low culture - Pluta, Joanna (Biografie nieoczywiste: Przełom, kryzys, transgresja w perspektywie interdyscyplinarnej, 2018)
The article aims at the presentation of the biography of Edward D. Wood Jr. And at the exploration of the causes of his popularity. Tim Burton’s film Ed Wood is the major subject of this analysis. The film mentioned spans six years in the director’s life during which his most renown films were created. Ed Wood has been remembered by the public opinion as „The Worst Director of All Time” (Medved, 1978), mainly because of his B-movie Plan 9 from Outer Space (1959). The reseasons for choosing this person as the subject of Burton’s film biography as well as Wood’s features which are probably the most attractive for the audience are indicated. Amongst tchem are: the attainment of success despite the lack of skills and talent, charisma, self-confidence and the creation of films having „less to do with artistic achievement than with [Wood’s] unblinking faith in his artistic vision” (Lupo, Anderson, 2008, p. 105). The article contains also the description of Wood’s personality and life (both with the traits which distuinguish him among the others), as well as of the extra-ordinary features of his biography (such as film-makers’ ironic but uncynical attitude towards Ed Wood).